Development of novel aptamer‐based enzyme‐linked apta‐sorbent assay (ELASA) for rapid detection of mariculture pathogen Vibrio alginolyticus. Issue 11 (26th August 2019) - Yu, Qing; Liu, Mingzhu; Xiao, Hehe; Wu, Siting; Qin, Xianling; Ke, Ke; Li, Siqiao; Mi, Huizhi; Shi, Deqiang; Li, Pengfei
Abstract: As the major opportunistic pathogen to both marine animals and humans, Vibrio alginolyticus ( V. alginolyticus ) has caused heavy economic losses to mariculture. ssDNA aptamer VA2 targeting live V. alginolyticus was generated by systematic evolution of ligands by exponential enrichment (SELEX) technology in our previous study. In this study, we first developed aptamer (VA2)‐based enzyme‐linked apta‐sorbent assay (VA2‐ELASA) for rapid detection of mariculture pathogen V. alginolyticus . The VA2‐ELASA could achieve the rapid detection for V. alginolyticus infection with high specificity and sensitivity. The VA2‐ELASA could specifically identify V. alginolyticus, but not other non‐target bacterial strains. VA2‐ELASA could detect V. alginolyticus at the concentration of 5 × 10 4 /ml, the incubation time short to 1 min and the incubation temperature as high as 45°C, which proved sensitivity and stability of the novel VA2‐ELASA in this study. It took less than one hour to accomplish the detection process by VA2‐ELASA. The characteristics of specificity, sensitivity and easy operation make VA2‐ELASA a novel useful technology for the rapid diagnosis of pathogen V. alginolyticus in mariculture.